Overview of the CRP Commissioned evaluation on the value chain approach of Livestock and Fish - Child, K. (International Livestock Research Institute, 2015)
By Keith Child to the CGIAR Research Program on Livestock and Fish review and planning meeting, 23-26 March 2015